Mathematics Learning Using Zoom Cloud Meeting During the Covid-19 Pandemic for Elementary School Students - Prima Luqman Prasetya; Fitri Nur Mahmudah (Institut Agama Islam Negeri Palopo, 2021)
The purpose of this study was to determine the implementation of mathematics learning in elementary school students by using zoom cloud meetings during the Covid-19 pandemic. The method used in this research is qualitative. The technique of collecting data using participatory observation and using observation guidelines. The place of this research is SD Muhammadiyah Prambanan. The research subjects are 15 grade students of elementary school with a total of 5 people. The technique of determining participants using purposive. Data analysis was used with the assistance of atlas.ti software version 8. The results of this study provide information that learning mathematics using the zoom cloud meeting consists of three things, namely learning conditions, the implementation process, and learning outcomes. Where each finding has its respective sub-components. The findings of this study can be used as a teacher strategy in developing abilities and competencies in teaching elementary school students using the zoom cloud meeting platform. The recommendations of this study are for elementary school teachers in any discipline. The strategy in the results of this study can be used as an indicator for achieving success in learning.